THE AMERICAN INDIVIDUALISM AS REFLECTED IN GARDNER’S AS THE MAIN CHARACTER IN FILM THE PURSUIT OF HAPPINESS: A SOCIOLOGICAL APPROACH - Londa, Erni N; Liru, Marianus W; Doi, Maksimilianus (Lantern: Journal of Language and Literature, 2022)
The purpose of the study was to find out the aspects of American Individualism as reflected in Gardner as the main character in film The Pursuit of Happiness. This film directed by Gabriele Muccino which the story is taken from the real life by an author named Chris Gardner. This film raises issues in social life, especially in the main character Chris Gardner regarding aspects of American individualism. This research used descriptive-qualitative method. In this research conducted stages of research in collecting the data, they are: first, watching the film carefully, writing the data on utterance and actions in accordance with the problem formulation and then identifying utterance and actions. This study used the theory of Emerson (1941) about self-confidence and self-reliance. The results showed that there were three forms of self-confidence (personal ability, self-concept and social interaction) and self-reliance (responsibility). The aspect of individualism experienced by Chris Gardner is to show the community and every individual about the struggle and hard work that requires self-reliance and self-confidence. American Individualism, self-reliance, self confidence